KOMPETISI MODA ANGKUTAN UMUM DARAT (KORIDOR KOTA PADANG PANJANG - PADANG, SUMATERA BARAT - Angelalia Roza; Andi Mulya Rusli; Muhammad Amrullah Saputra (Racic : Rab Construction Research, 2021)
Padang City is a city that is the center of economic and educational movement in West Sumatra. Meanwhile, Padang Panjang City is one of the cities that is currently preparing the younger generation to become the part that will cultivate the city well. Unlike the city of Padang, Padang Panjang City is a city that is currently one of the cities with culinary attractions that are in demand by the people of West Sumatra. This is a major attraction for the city trip. The purpose of this study is to identify the factors that will influence the choice of the community to use the land public transportation mode between Minibus and Travel Car from Padang Panjang to Padang, and to analyze the choice of modes to get the best travel mode of transportation. Travel attraction modeling is done using multiple linear regression equations with the help of the SPSS program. The characteristics of the community's journey to Padang Panjang City to Padang City were that the gender was male (58.5%), the age of the people who traveled 15-25 years (55.5%), high school education (52%), student community work (45 %), the total income is <IDR 1 million (50%), the most common mode to go to Padang city is both (49%), the reason for choosing the mode is cost (39.0%), and the most frequent departure is 2x a week (30 %). The factors that influence the travel attraction (y) are influenced by income (X1), travel time (X2), convenience (X3). with a value of R 2 = 0.516